2021
DOI: 10.3389/fcell.2021.684125
|View full text |Cite
|
Sign up to set email alerts
|

CircGNG4 Promotes the Progression of Prostate Cancer by Sponging miR-223 to Enhance EYA3/c-myc Expression

Abstract: Patients diagnosed with prostate cancer often have a poor prognosis and limited treatment options, as the specific pathogenesis remains to be elucidated. Circular RNA (circRNA) is a type of non-coding RNA that interacts with microRNA (miRNA/miR) and transcription factors to regulate gene expression. However, little is known about specific circRNAs that serve roles in the pathogenesis of prostate cancer. Findings of the present study confirmed that circRNA G protein subunit γ 4 (circGNG4) was upregulated in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“… 32 , 33 Bioinformatic analysis has shown that MYC is not a direct target of miR-342. However, the 3′-UTR of EYA3, which increases MYC protein stability by dephosphorylating threonine 58 (Thr58) and phosphorylating serine 62 (Ser62) of MYC via protein phosphatase 2A, 34 , 35 harbors an miR-342 recognition site ( Figure S7 A). Next, we assessed whether miR-342 influences MYC stability.…”
Section: Resultsmentioning
confidence: 99%
“… 32 , 33 Bioinformatic analysis has shown that MYC is not a direct target of miR-342. However, the 3′-UTR of EYA3, which increases MYC protein stability by dephosphorylating threonine 58 (Thr58) and phosphorylating serine 62 (Ser62) of MYC via protein phosphatase 2A, 34 , 35 harbors an miR-342 recognition site ( Figure S7 A). Next, we assessed whether miR-342 influences MYC stability.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] circGNG4 worked as a potent driver in prostate cancer by EYA3/c‐Myc pathway via miR‐223 competition. [ 15 ] Circ_001422 sponged miR‐195‐5p to expedite the tumorigenesis and progression of osteosarcoma by fibroblast growth factor 2/phosphatidylinositol 3‐kinase pathway. [ 16 ] In NSCLC, circ_0003222 and circ_0060937 have been claimed to be aberrantly expressed and are strongly linked to the occurrence of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are abnormally expressed in many malignant tumours and have critical roles in regulation of various pathological and physiological processes in cancers (Arnaiz et al, 2019; Vo et al, 2019). Additionally, some circRNAs have been found to be implicated in PCa tumorigenesis via acting as tumour promoters or suppressors (Wang et al, 2021; Xu et al, 2021). Circ_0076305 is derived from progastricsin (PGC) gene and located on chr6:41704448–41712252.…”
Section: Introductionmentioning
confidence: 99%